2023
DOI: 10.1159/000531630
|View full text |Cite
|
Sign up to set email alerts
|

Sex as a Factor in Murine Radiation Research: Implications for Countermeasure Development

Gregory P. Holmes-Hampton,
Vidya P. Kumar,
Kaylee Valenzia
et al.

Abstract: There is an increased threat of exposure to ionizing radiation, in the event of such exposure the availability of medical countermeasures will be vital to ensure the protection of the population. Effective countermeasures should be efficacious across a varied population and most importantly amongst both males and females. Radiation research must be conducted in animal models which act as a surrogate for the human response. Here we identify differences in survival in male and female C57BL/6 in both a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…To utilize this model for evaluation of potential countermeasures and to be able to compare it to TBI models already published for the same purpose, LD 50/30 was also determined. As most deaths were between days 6 and 12 after PBI, the LD 50/30 and LD 50/10 values were relatively close and have the same trend where the dose was slightly lower in males (14.3 Gy) than in females (14.5 Gy), suggesting females are radioresistant compared to male mice, which is in concurrence with data from same strain exposed to TBI (48). The time of death reported here can be correlated to solely GI death as published by other researchers (23); this is also supported by secondary endpoints of GI-ARS, as described here.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To utilize this model for evaluation of potential countermeasures and to be able to compare it to TBI models already published for the same purpose, LD 50/30 was also determined. As most deaths were between days 6 and 12 after PBI, the LD 50/30 and LD 50/10 values were relatively close and have the same trend where the dose was slightly lower in males (14.3 Gy) than in females (14.5 Gy), suggesting females are radioresistant compared to male mice, which is in concurrence with data from same strain exposed to TBI (48). The time of death reported here can be correlated to solely GI death as published by other researchers (23); this is also supported by secondary endpoints of GI-ARS, as described here.…”
Section: Discussionsupporting
confidence: 86%
“…As suggested by many researchers (48,51,52), we observed a difference in radiation sensitivity between male and female mice with respect to LD 50/30 doses. Males were slightly more radiosensitive.…”
Section: Discussionsupporting
confidence: 78%
“…As previous studies have explored the impact of neutron exposures and dose rate (e.g., refs and see ref for a compiled list), here we compared metabolite levels in urine and serum from male and female C57BL/6 mice following a sham irradiation, TBI of either 4 or 8 Gy, and an upper body irradiation (UBI) and lower body irradiation (LBI) with 8 Gy using a VHDR. We predicted, as we have seen in previous studies, that although certain responses to radiation injury will be specific to factors such as sex or exposure type, there will be metabolites that are universally changed irrespective of these factors. Once elucidated, these metabolites can be refined into multiplex panels to aid in high-throughput biodosimetry.…”
Section: Introductionmentioning
confidence: 56%
“…Recently, work from our lab analyzing survival curves in male and female mice from various studies demonstrated a slight yet statically significant increase in female mice survival compared to male mice survival, a trend which was also observed in the current work. 34 It is expected that mice manifest DEARE including abnormalities and pathological changes in major tissues and organs as long-term effect following radiation exposure. While comparing BW increases over 6 months post-TBI in male vs. female mice, BW gain was similar in both sexes.…”
Section: Discussionmentioning
confidence: 99%